1985
DOI: 10.1007/bf00343785
|View full text |Cite
|
Sign up to set email alerts
|

Temporal evolution of hypoxis-ischaemic brain lesions in asphyxiated full-term newborns as assessed by computerized tomography

Abstract: Hypoxic-ischaemic brain lesions may be detected as low density (LD) areas by means of computerized tomography (CT), but the clinical significance of such LD areas has been controversial. Since timing might be a critical factor, we studied the temporal evolution of LD areas in 9 asphyxiated term babies who had had two or more CT, and compared the changes to the neurodevelopmental outcome. Scans were classified according to the elapsed time after asphyxia as early (day 1-7, n = 6), intermediate (week 2-4, n = 7;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…When the same Quantitative assessment of LD areas was done on first week CT scans, almost no relationship with the outcome was found. This confirms our previous observation that developmentally relevant hypoxic-ischaemic lesions cannot be detected as LD areas during the first week (Lipp-Zwahlen et al 1985), and explains why Lud~'ig et al (1980) could not find any pathological meaning of LD areas. In the cases presented here, the intermediate CT seems to predict the outcome of asphyxiated babies with great accuracy, much like CT scans done in the second week after stroke in children (Gates et al 1982).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…When the same Quantitative assessment of LD areas was done on first week CT scans, almost no relationship with the outcome was found. This confirms our previous observation that developmentally relevant hypoxic-ischaemic lesions cannot be detected as LD areas during the first week (Lipp-Zwahlen et al 1985), and explains why Lud~'ig et al (1980) could not find any pathological meaning of LD areas. In the cases presented here, the intermediate CT seems to predict the outcome of asphyxiated babies with great accuracy, much like CT scans done in the second week after stroke in children (Gates et al 1982).…”
Section: Discussionsupporting
confidence: 90%
“…The exception, who later sufTered from tetraspas- ticity and atethosis, had severe but restricted LD areas that largely spared the cortical rim. The rcason for such a relative-Iy low LD score inspite ofa severe handicap, might be that the CT (from day 29) was done during aperiod in which proliferative repair processes begin to mask the CT-visibility of cortical and white matter lesions, as documented by us elsewhere (Lipp-Zwahlen et al 1985).…”
Section: Discussionmentioning
confidence: 88%
“…sonography (17), near infrared spectroscopy (36), positron emission tomography (33), P-and H-magnetic resonance spectroscopy (2,23,27), ultrasound (3,29) and computed tomography (CT) (1,9,18,19). High sensitivity and specifity of MRI in detecting abnormalities in asphyxiated infants and young children has been demonstrated in several prospective studies (7,12,13,20).…”
mentioning
confidence: 99%
“…Therefore we followed prospectively cerebral blood flow velocity in both perinatally asphyxiated and healthy newborns with a gestational age of at least 34 weeks in the first week of life and compared the results of both groups. The infants were matched for birth weight and gestational age.To study our hypothesis that especially cerebral oedema plays an important role in the abnormal changes of cerebral blood flow velocity, we performed serial real-time ultrasonographic and computerized axial tomographic studies (if indicated) of the brain for detection of infarctions, parenchymal haemorrhage and of cerebral oedema [19,31,32,[42][43][44]. …”
mentioning
confidence: 99%